(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2015)
This study elaborates in detail the concept istihsan (juristic preference) to give a comprehensive explanation of this concept, both theoretically and of the actual application of this concept in the Islamic law and Syariah Courts in Malaysia. This study shows that istihsan is one of the sources that is recognized under Islamic law, while disagreement between scholars is only concerning its technical definition. This finding is further reinforced with the analysis of reported cases in the syariah c ourts in Malaysia, which indicate the use of istihsan indirectly in the court. In addition, the study also concludes that the provisions of the law itself authorize judges to indirectly apply this concept. Keywords: istihsan, qiyas, source of law, syariah court, judge